SCIENTIFIC AND THEORETICAL BASIS AND FACTORS OF ENSURING MACROECONOMIC STABILITY (European Journal of Economics, Finance and Business Development, 2025)
There are many factors that ensure macroeconomic stability, but among them, economic and financial, monetary and credit, and social factors are of particular importance, but among them, financial factors have the greatest influence. This article analyzes macroeconomic stability and financial factors to achieve it, analyzes some directions of its provision in the economy of Uzbekistan, and considers issues related to solving existing problems.